Recognition of prior learning: the participants' perspective. Issue 2 (3rd May 2016) - Miguel, Marta C.; Ornelas, José H.; Maroco, João P.
ABSTRACT: The current narrative on lifelong learning goes beyond formal education and training, including learning at work, in the family and in the community. Recognition of prior learning is a process of evaluation of those skills and knowledge acquired through life experience, allowing them to be formally recognized by the qualification systems. It is a central aspect of lifelong learning. This mixed-method study aimed to understand what changes were perceived by participants due to their participation in a program of recognition of prior learning in Portugal – grade 9 and grade 12 equivalence, resulting in certification. Content analysis of focus groups and interviews identified changes at personal, educational and training, and professional levels, but gains primarily occurred at the personal level. A scale of changes in participants was created to measure the effect of recognition of prior learning at an individual level of analysis. Descriptive statistics revealed mainly effects in terms of learning, increases in confidence, realization of the prior knowledge and skills, valorization of the life experience, and motivation to further learning.